A global approach to multi-axis swept mesh generation. (2017) - Wu, Haiyan; Gao, Shuming; Wang, Rui; Ding, Mao
Abstract: The sweeping algorithm is a classical algorithm that can generate high quality hexahedral meshes for swept volumes. However, the traditional sweeping algorithm can only generate single axis swept meshes. In order to expand the scope of the model that sweeping algorithms are applicable to, this paper proposes a global multi-axis swept mesh generation approach, which can robustly generate hexahedral meshes for solid models composed by multi-axis swept volumes. We first globally generate all the surface meshes by applying an optimized structured quadrilateral mesh generation algorithm. After that we generate a swept mesh for each swept volume. Finally, we determine an appropriate way to optimize the topology of the generated mesh so as to improve the mesh quality. The experimental results show the effectiveness and efficiency of the proposed method.